[(3TQM fXe eJf GdGSJYGQGJ(B]s - (3CMeO Hf YHO GdaJGM Gdedhjs; (3GdeLjQj , TgGH GdOjf CHh GdYHGS CMeO Hf YHO GdaJGM Hf jhSa Hf YeQ Gdedhj GdTGaYj,J (B1181 (3g` s ((3GdeLjQi , TgGH GdOjf CHh GdYHGS CMeO Hf YHOGdaJGM Hf jhSa Hf YeQ Gdedhi GdTGaYi ; J (B1181 (3g` s)
(3ChdgG (B:s
(3CeG HYO ajbhd GdYHO bO fXeJ ajeG eVi QSGdI GdYdGeI GdSeQbfOi ai GdGSJYGQGJ p hgPG TQlM eaJGlM dcfhpR ZhGeV CSQGQg s
(3BNQgG (B:s
(3hGMOkG Ch CcKQ ef hGMO hGdMeO ddg s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3GdTGQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B152 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B278s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdHdGZIs